Oral tranexamic acid for an additional 24 hours postoperatively versus a single preoperative intravenous dose for reducing blood loss in total hip arthroplasty: results of a randomized controlled trial (TRAC-24). (1st July 2021) - Magill, Paul; Hill, J. C.; Bryce, Leeann; Martin, Una; Dorman, Al; Hogg, Rosemary; Campbell, Christina; Gardner, Evie; McFarland, Margaret; Bell, Jennifer; Benson, Gary; Beverland, David
Abstract : Aims: A typical pattern of blood loss associated with total hip arthroplasty (THA) is 200 ml intraoperatively and 1.3 l in the first 48 postoperative hours. Tranexamic acid (TXA) is most commonly given as a single preoperative dose only and is often withheld from patients with a history of thromboembolic disease as they are perceived to be "high-risk" with respect to postoperative venous thromboembolism (VTE). The TRanexamic ACid for 24 hours trial (TRAC-24) aimed to identify if an additional 24-hour postoperative TXA regime could further reduce blood loss beyond a once-only dose at the time of surgery, without excluding these high-risk patients. Methods: TRAC-24 was a prospective, phase IV, single centre, open label, parallel group, randomized controlled trial (RCT) involving patients undergoing primary unilateral elective THA. The primary outcome measure was the indirect calculated blood loss (IBL) at 48 hours. The patients were randomized into three groups. Group 1 received 1 g intravenous (IV) TXA at the time of surgery and an additional oral regime for 24 hours postoperatively, group 2 only received the intraoperative dose, and group 3 did not receive any TXA. Results: A total of 534 patients were randomized, with 233 in group 1, 235 in group 2, and 66 in group 3; 92 patients (17.2%) were considered high-risk. The mean IBL did not differ significantly between the two intervention groups (848.4 ml (SD 463.8) for group 1, and 843.7 ml (SD 478.7) for group 2; mean difference -4.7 ml (95% confidence interval -82.9 to 92.3); p = 0.916). No differences in mortality or incidence of VTE were observed between any group. Conclusion: The addition of oral TXA for 24 hours postoperatively does not reduce blood loss beyond that achieved with a single 1 g IV perioperative dose alone. There may be a clinically relevant difference in patients with a normal BMI, which warrants further investigation. Critically, there were no safety issues in patients with a history of thromboembolic, cardiovascular, or cerebrovascular disease. Cite this article: Bone Joint J  2021;103-B(7):1197–1205.